Pengaruh Penggunaan Media Pembelajaran Interaktif Terhadap Motivasi Belajar Siswa pada Mata Pelajaran SKI Kelas XI: (Studi Kasus di Kelas XI IPA Madrasah Aliyah 1 Kampar) - Riskiyah Riskiyah; Rodiah Rodiah; Romadlon Khusnul Kirom (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study aims to analyze the influence of the use of interactive learning media on students' learning motivation in the subject of Islamic Cultural History (SKI) in class XI Science Madrasah Aliyah 1 Kampar. The background of this research is based on the low learning motivation of students in SKI learning who still uses conventional methods. The research method used is Classroom Action Research (PTK) with a quantitative and qualitative approach. Data was collected through observation, questionnaires, interviews, and formative tests. The results showed that the use of interactive media increased students' learning motivation by 85%, increased students' active involvement in class discussions, and increased the average score of students from 68 to 82. In addition, this study confirms that the use of interactive media contributes to improving students' conceptual understanding and memory of subject matter. The conclusion of this study is that interactive learning media is an effective method to increase students' learning motivation in SKI subjects.